Magnetic resonance enterocolonography in detecting erosion and redness in intestinal mucosa of patients with Crohn's disease. Issue 4 (April 2015) - Sato, Hirokazu; Tamura, Chiharu; Narimatsu, Kazuyuki; Shimizu, Motonori; Takajyo, Takeshi; Yamashita, Masataka; Inoue, Yasushi; Ozaki, Hayato; Furuhashi, Hirotaka; Maruta, Koji; Yasutake, Yuichi; Yoshikawa, Kenichi; et al.
Abstract: Background and Aim: In Crohn's disease (CD), assessment of disease activity and extension is important for clinical management. Endoscopy is the most reliable tool for evaluating disease activity in these patients and it distinguishes between lesions based on ulcer, erosion, and redness. Magnetic resonance imaging (MRI) is less invasive than endoscopy; however, the sensitivity of MRI in detecting lesions is believed to be lower, and whether MRI can detect milder lesions has not been studied. The aim of this study was to compare the detection ability of magnetic resonance enterocolonography (MREC) with ileocolonic endoscopy in patients with CD. Methods: A total of 27 patients with CD underwent both MREC and ileocolonoscopy. There were 55 lesions (18 ileum and 37 colon) endoscopically detected, and the findings of MREC were compared with each ileocolonoscopic finding to determine sensitivity and specificity. Results: For a positive lesion defined as having at least one of the following: wall thickness, edema, diffusion‐weighted imaging (DWI) high intensity and relative contrast enhancement (RCE) on MREC, the sensitivities were 100% for ulcer, 84.6% for erosion, and 52.9% for redness, suggesting an ability to detect milder lesions such as erosion or redness. Moreover, RCE values were well correlated with the severity of endoscopically identified active lesions. Conclusion: MREC findings may be useful not only for evaluation of ulcers, but also for detection of endoscopically identified milder lesions in CD, suggesting a clinical usefulness of MREC for disease detection and monitoring.